Dynamic Quality Control for Transform Domain Wyner-Ziv Video Coding. (26th March 2009) - Sofke, Sören; Pereira, Fernando; Müller, Erika
Abstract : Wyner-Ziv is an emerging video coding paradigm based on the Slepian-Wolf and Wyner-Ziv theorems where video coding may be performed by exploiting the temporal correlation at the decoder and not anymore at the encoder as in conventional video coding. This approach should allow designing low-complexity encoders, targeting important emerging applications such as wireless surveillance and visual sensor networks, without any cost in terms of RD performance. However, the currently available WZ video codecs do not allow controlling the target quality in an efficient way which is a major limitation for some applications. In this context, the main objective of this paper is to propose an efficient quality control algorithm to maintain a uniform quality along time in low-encoding complexity WZ video coding by dynamically adapting the quantization parameters depending on the desired target quality without any a priori knowledge about the sequence characteristics. This objective will be reached in the context of the so-called Stanford WZ video codec architecture which is currently the most used in the literature.